Peran Pemimpin Kelompok Sebagai Katalisator Dinamika Dalam Psikoedukasi Kelompok: Tinjauan Literatur - Nadya Azhari Rambe; Awalya Awalya; Muslikah Muslikah (Educational Guidance and Counseling Development Journal, 2026)
This study aims to analyze the role of group leaders as catalysts of group dynamics in psychoeducation through a Systematic Literature Review (SLR) approach. The method used refers to the PRISMA protocol, with stages of identification, screening, eligibility, and inclusion. Data sources were obtained from Google Scholar, ScienceDirect, SpringerLink, SAGE Journals, and MDPI, with publications spanning 2019–2026. Based on the selection process, 10 articles were selected and analyzed using thematic analysis techniques. The results indicate that the effectiveness of group psychoeducation is significantly influenced by the quality of the group dynamics established during the process. In this regard, the group leader acts as a catalyst, actively facilitating, directing, and optimizing interactions between members. This role includes facilitating dynamics, creating a safe psychological climate, managing interactions and conflicts, and constructing an inclusive interaction space. These findings confirm that group leaders act not merely as passive facilitators but as active agents accelerating the process of psychological change through effective group dynamics. Therefore, strengthening group leadership competencies is a crucial aspect in improving the quality of group psychoeducation services.